Pipeline slot based fast rerouting scheme for delay optimization in duty cycle based M2M communications - Li, Qiaoyan; Liu, Anfeng; Wang, Tian; Xie, Mande; Xiong, Neal N. (Peer-to-peer networking and applications, 2019)
In recent years, with the development of networked Cyber-Physical Systems (CPSs), wireless sensor networks (WSNs), as an important carrier of CPSs, has been applied more and more. In WSNs, many applications require low delay and high reliability for routing the sensing data to sink. Due to the lossy nature of wireless channels, rerouting schemes are often applied to ensure reliable data collection for mission-critical applications. However, rerouting together with multi-hop routing in duty cycle base WSNs will make designing a low delay routing scheme a challenge issue. In this paper, a Pipeline Slot based Fast Rerouting (PSFR) Scheme is proposed to reduce delay in duty cycle based WSNs. The main innovation points of PSFR scheme are as follows: (a) In duty cycle based WSNs, the major delay is caused by the sleep delay when nodes in the route forwarding to next hop node. Therefore, in PSFR scheme, we add a sequential active (SA) slot at the next hop node which is active at the next slot of the active slot of the previous node, which enables the previous node to forward packets to the next hop node in the slot right after receiving packet in active slot and greatly reduces sleep delay. (b) The second, in PSFR scheme, the backup path is designed beforehand in a less stringent pipeline active slot, so the packet can reach the sink with a relatively low delay when rerouting. (c) More importantly, in PSFR scheme, the added SA slots use the residual energy of peripheral nodes, which means they reduce the routing delay without decreasing network lifetime. After sufficient theoretical analysis and experiment, results show that the PSFR scheme can reduce the delay by more than 58.215% in the experiment networks without reducing the network lifetime, and the PSFR scheme can improve the energy utilization of network by more than 27.66%.